Research of Dependence of Changes Values of Slipping of Tire in the Process of its Deterioration - S.I. Medveditskov (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2013)
Dependences of changes values of slipping of automobile tires of various models and period of storage in a contact spot in a leading mode in process of increase of small corners of withdrawal, as the result of deterioration of drawing of a protector are received.